THE DEVELOPMENT OF VIDEO RESTORATION APPLICATION - Agus Wibawantara, Gusti Ngurah Made (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
Restoration technique besides can be applied in image, it also can be applied in video. Basically, video is a moving image. In the old video or a video that has been old is usually getting degradation which likely happened in an image. The damage on the video is usually in the form of noise salt and pepper, the quality of lighting which is not good where there is an obscure area in several parts and the picture of the video whichis sharp less.In this study, using five different methods of image processing, namely median filtering, contrast stretching, logarithmic transformation, image erosion and image sharpening. Median filter method used to handle the salt and pepper noise, contrast stretching used to improve image contrast, a logarithmic transformation used to increase the brightness of the image. Erosion method used to remove white spots noise on the image that has a black background and simple white objects. Image sharpening used to sharpen the edges of blurred image.Restoration techniques on the video was done in a way to extract the videobecame frames and audio file. These frame then restore using selected processing methods. The restored frame then render with the audio files into a video file. From the result data of system testing proved that a video can be given more than one restoration method based on the damage type of the video.